If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -7 + -15 = 6 Reorder the terms: -7 + -15 + X = 6 Combine like terms: -7 + -15 = -22 -22 + X = 6 Solving -22 + X = 6 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + X = 6 + 22 Combine like terms: -22 + 22 = 0 0 + X = 6 + 22 X = 6 + 22 Combine like terms: 6 + 22 = 28 X = 28 Simplifying X = 28
| 4x-14+2x+8= | | 7(x+2)=2x+17 | | X-7-15=15 | | 70/10=2x+4(-3x) | | (x-2)+(y-2.5)=8 | | 2x^2-2x+38=0 | | 14n-2-13n-15=3 | | 5n^2+2n+7= | | -4x^3+12x^2-16=0 | | 23c^2+56c+10=0 | | (2w^2-2)/(w^2-4w-5) | | 2z^2+19z+20=0 | | 11(a-3)=-2-9 | | 3x-12+2x-3= | | (5w-8)(4+w)=0 | | 3/4y=-21 | | Y=2+x+3 | | 5*3x=42 | | 175-125+43425=45900-175 | | -4u/7=-16 | | y=5+2x-16 | | 123*1/4= | | 3m+20=4m+10 | | 32pt=gal | | 18-f/3=-7 | | 2+6x=0 | | lb=64oz | | (9y^4-6y^3-5y+7)+(18y^4-2y^3-7y+8)= | | (y-1)(y+9)= | | 98-m=44 | | -20=-5/9w | | y=-2x^2-7x-6 |